A working typology of response options to manage environmental change and their scope for complementarity using an Ecosystem Approach. Issue 52 (October 2015) - Brown, Iain; Everard, Mark
Highlights: A diverse range of response options to manage environmental change are characterised based upon key attributes. Attributes are used to produce a typology of the main types of intervention or influence. The typology is referenced against a systems framework based upon an integration of ecosystem services and DPSIR. The systems framework and typology provide a working structure to highlight how response options can be used as complementary and systemic initiatives. This structure is consistent with and guided by the principles of the Ecosystem Approach. Abstract: A diverse range of response options is available for decision-makers to manage environmental change and meet sustainability objectives. These can include inter alia: top-down statutory regulation and levies; bottom-up initiatives including quality assurance networks or community-based partnerships; formal incentives; and voluntary market-based schemes such as 'payments for ecosystem services' or offsetting. Each type of response option has a distinct set of characteristics, which suggests that they may be best suited to different contexts rather than presumed to be effective in all circumstances. These attributes are used to develop a working typology to help understand the strengths and weaknesses of different response types, particularly regarding adaptation to long-term change and handling of uncertainty. To facilitate this, response types are referenced from a socio-ecological systems perspective using a refined version of the DPSIR integrated assessment framework to incorporate ecosystem functions and services. This shows that some responses are more clearly associated with maintaining resilience of natural functions, whilst others are directed at human-defined services. The role of stakeholders in response options can also be distinguished such as comparing mandatory or voluntary initiatives. Polluter-pays approaches are therefore distinguished from beneficiary-pays approaches. The typology can therefore provide a working reference framework for recognising complementary rather than conflicting interventions, as guided by the holistic principles of the Ecosystem Approach.